IDENTIFICATION OF FRESHWATER GOBY SPECIES FROM THE BIAK AND KOYOAN RIVERS, LUWUK BANGGAI, CENTRAL SULAWESI - Gani, Abdul; Bakri, Achmad Afif; Adriany, Devita Tetra; Nurjirana, Nurjirana; Herjayanto, Muh.; Bungalim, Monicha Indrasari; Ndobe, Samliok; Burhanuddin, Andi Iqbal (Hasanuddin University, 2019)
Sulawesi is an island famous for its biodiversity, including many endemic species. In particular, Sulawesi has the highest number of gobies in the world, including species with potential as food and/or ornamental fishes. The exploration of freshwater ichthyofauna is important in the context of Indonesian and global biodiversity. This research aimed to identify gobies found in the Luwuk Banggai area of Central Sulawesi, as a contribution to the exploration of Indonesian ichthyofaunal biodiversity. Gobies were sampled from January to March 2019 in the Biak and Koyoan Rivers. The sampled fish were measured and identified based on morphological characteristics. A total of 52 specimens were collected, and identified as belonging to 17 species within two families, the Gobiidae and Eleotridae. Gobies from the Koyoan River comprised 32 specimens from 8 species, while 20 specimens belonging to species were found in the Biak River. Only two species were found in both rivers: Stiphodon semoni and Sicyopterus lagocephalus. These results augment the body of knowledge regarding the presence and distribution of gobies in Indonesia